TEACHING AND LEARNING MULTIPLICATION OF MULTI-DIGIT NUMBERS IN REALISTIC MATHEMATICS EDUCATION (RME) - Dian Armanto (Study Program of Mathematics Education of Unimed Postgraduate Program, 2008)
This study developed a learning trajectory of the multiplication of multi-digit numbers in Indonesian primary schools using Realistic Mathematics Education (RME). It was the third cyclic process of the developmental research process conducted in 4 primary schools in Medan and Yogyakarta in the academic year of 2000. This study produced a local instruction theory of teaching multiplication of multi-digit numbers in primary schools in Indonesia. The learning trajectory was begun by introducing the repeated addition of ten numbers, the multiplication by 10, the multiplication by multiples of ten, and the standard multiplication algorithm. This local basic learning trajectory theory of multiplication was opened for adjustment and justification and it was functioned as guidance for other researcher in conducting the next developmental research